Improvement of liver transplantation by reducing preservation-reperfusion injury - van As, Arjan Bastiaan (Department of Surgery, 2018)
The liver differs from other solid organs in that it has a dual blood supply, receiving arterial blood via the hepatic artery and venous blood via the portal vein. The reperfusion injury which occurs after ischemia, has been studied to only a limited extent in the liver. In particular, the relative contribution of the portal venous blood and the hepatic arterial blood to the reperfusion injury has not been documented previously. During liver transplantation, implantation of the new liver is achieved by anastomosing the suprahepatic vena cava, the infrahepatic vena cava and the portal vein. At this stage, the liver is reperfused with portal venous blood only. Thereafter the hepatic arterial anastomosis is undertaken. The delay in providing the liver allograft with arterial blood will depend upon the difficulty in the dissection of the hepatic artery. The impact of the delay in rearterialization of the liver allograft has not been studied previously. Currently, the University of Wisconsin Solution is the gold standard for liver preservation. Celsior is a new cardioplegic solution, which has also been suggested for use for liver preservation. However, its role as a liver preservation solution has been studied to a limited extent. The aim of this study was: 1. To document the reperfusion injury after liver transplantation. 2. To document the relative contribution of the portal venous blood and the hepatic arterial blood to the reperfusion injury. 3. To investigate the impact of early rearterialization on the reperfusion injury after liver transplantation. 4. To investigate the effect of the new preservation solution, Celsior, on the reperfusion injury after liver transplantation. Large White X-Landrace pigs were subjected to orthotopic liver transplantation. The donor liver was stored in Eurocollins solution for 3 hours. The animals were randomly allocated to either rearterialization 60 minutes after portal reperfusion, rearterialization 20 minutes after portal reperfusion, simultaneously portal and arterial reperfusion, and rearterialization 20 minutes before portal venous reperfusion. In another experiment, the donor livers were stored in either Eurocollins solution, University of Wisconsin Solution, or Celsior. Blood samples were taken at various intervals and subjected to the following biochemical investigations. Malondialdehyde and vitamin A were used as markers of reperfusion injury. Hyaluronic acid levels were used as markers of endothelial cell function. Serum AST was used as a marker of hepatocellular injury. In summary, these studies showed that there was a significant reperfusion injury after portal venous reperfusion with no additional injury after rearterialization. Early rearterialization also resulted in a lesser reperfusion injury. There was also less hepatocellular injury with early rearterialization. Histological evidence of injury was also less in the livers which were rearterialized early. In addition, the livers preserved in Celsior had evidence of a lesser reperfusion injury. Thus in conclusion, in liver transplantation early rearterialization might result in better early graft function.